Respuesta :

x

=

42

and  

y

=

24

Explanation:

Step 1) Solve the second equation for  

x

:

x

+

2

y

2

y

=

6

2

y

x

+

0

=

6

2

y

x

=

6

2

y

Step 2) Substitute  

6

2

y

for  

x

in the first equation and solve for  

y

:

3(-6 - 2y) + 5y = 6#

18

6

y

+

5

y

=

6

18

y

=

6

18

+

18

y

=

6

+

18

0

y

=

24

y

=

24

y

1

=

24

1

y

=

24

Step 3) Substitute  

24

for  

y

in the solution to the second equation in Step 1) and calculate  

x

:

x

=

6

(

2

24

)

x

=

6

+

48

x

=

42

This is the answer for your question above
Ver imagen nessa1012
ACCESS MORE